2018
DOI: 10.1007/s00128-018-2374-9
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Pollution and Ecological Risk Assessment of the Agriculture Soil in Xunyang Mining Area, Shaanxi Province, Northwestern China

Abstract: Mining is considered to be one of the most significant sources of environmental pollution with regard to heavy metals. Mineral mining causes large quantities of mercury, cadmium, and other elements to be released into the environment and naturally poses a serious threat to environment. This paper will analyze the pollution status of agricultural soil caused by the mining of heavy metals in various mining areas in the Xunyang County in the Shaanxi Province of China, an area in famous for its resource mining. Eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 26 publications
1
27
0
2
Order By: Relevance
“…Heavy metals and metalloid are considered to be the most dangerous contaminants to the environment on account of their toxicity to the soil, and they reduce the sustainability of the environment [1]. According to the National Soil Bulletin Survey in 2014, soil pollution caused by heavy metals and metalloid is prevalent in China, and the soil quality of cultivated land has been gradually decreasing [2]. The national total soil over-standard rate is 16.1%.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals and metalloid are considered to be the most dangerous contaminants to the environment on account of their toxicity to the soil, and they reduce the sustainability of the environment [1]. According to the National Soil Bulletin Survey in 2014, soil pollution caused by heavy metals and metalloid is prevalent in China, and the soil quality of cultivated land has been gradually decreasing [2]. The national total soil over-standard rate is 16.1%.…”
Section: Introductionmentioning
confidence: 99%
“…In the north-eastern area of Hanoi, Vietnam, the agricultural soil presented a moderate environmental risk, and As and Cd had relatively high contribution rates [42]. In comparison, the potential ecological risk level [5], [22] and contribution order of the heavy metals [43][44] were anastomosis with former researchers' findings.…”
Section: Plos Onementioning
confidence: 54%
“…The potential risk status of farmland had been studied previously around the world. In the Xunyang area, the mean value of RI was 259, indicating a moderate ecological risk, and Hg and Cd were the main heavy metal elements, which posed a high and considerable potential ecological risk, respectively, in the agricultural area [5]. On the Qinghai-Tibet Plateau, the average concentrations of Hg and Cd were 0.28 and 0.68 mg/kg, respectively, which exceeded their background value 40 and 108 times, respectively, and the RI value in the soil ranged from 234.6 to 375.9.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Shanxi's coal production accounted for 26.6% (25.2-29.0%) of China's coal production during 2010-2017 [5,6], and coal consumption also accounted for 11.4% (10.8-11.9%) synchronously [7,8] (electronic supplementary material, table S1). Especially, coal mining is considered as one of the most significant sources of heavy metal contamination in surrounding areas [9,10]. A similar pattern was found that heavy metal pollution resulted from metal As and its carcinogenic risk of human in Shanxi's mines [11].…”
Section: Introductionmentioning
confidence: 56%